Determination of silver nanoparticle species released from textiles into artificial sweat and laundry wash for a risk assessment. Issue 4 (19th May 2017) - Kim, Jin Bae; Kim, Jong Yun; Yoon, Tae Hyun
ABSTRACT: Increasing use of nanomaterials for consumer products has induced growing concerns on their adverse effects on human health and the environment. To assess the environmental and human health risks of these nanoproducts, it is essential to identify physicochemical forms and quantify the amount of nanomaterials released from nanoproducts upon exposure to various environments. In this study, we have investigated the release assessment of nano-Ag textile products in terms of the total Ag content, and the distribution of Ag materials in the textile and the surrounding environment. The results suggest that the release of Ag nanomaterials from consumer products is less dependent on the total Ag content in the consumer product and depends significantly on the manufacturing processes of the consumer products as well as exposure environment. Based on these experimental results and a simple exposure model, the highest total exposure to particulate/dissolved Ag per use during sweating (1 h) was estimated to be 0.81/2.03 μg Ag/kg body weight with a standard body weight of 77 kg for a male. These results are fairly minimal human exposure and suggest that textiles containing Ag nanomaterials may be less of a concern in terms of human exposure to Ag nanomaterials.